Improving genetic diagnosis in Mendelian disease with transcriptome sequencing. - Cummings, Beryl B; Marshall, Jamie L; Tukiainen, Taru; Lek, Monkol; Donkervoort, Sandra; Foley, A Reghan; Bolduc, Veronique; Waddell, Leigh B; Sandaradura, Sarah A; O'Grady, Gina L; Estrella, Elicia; Reddy, Hemakumar M; et al. (Sci Transl Med, 2017)
Exome and whole-genome sequencing are becoming increasingly routine approaches in Mendelian disease diagnosis. Despite their success, the current diagnostic rate for genomic analyses across a variety of rare diseases is approximately 25 to 50%. We explore the utility of transcriptome sequencing [RNA sequencing (RNA-seq)] as a complementary diagnostic tool in a cohort of 50 patients with genetically undiagnosed rare muscle disorders. We describe an integrated approach to analyze patient muscle RNA-seq, leveraging an analysis framework focused on the detection of transcript-level changes that are unique to the patient compared to more than 180 control skeletal muscle samples. We demonstrate the power of RNA-seq to validate candidate splice-disrupting mutations and to identify splice-altering variants in both exonic and deep intronic regions, yielding an overall diagnosis rate of 35%. We also report the discovery of a highly recurrent de novo intronic mutation in that results in a dominantly acting splice-gain event, disrupting the critical glycine repeat motif of the triple helical domain. We identify this pathogenic variant in a total of 27 genetically unsolved patients in an external collagen VI-like dystrophy cohort, thus explaining approximately 25% of patients clinically suggestive of having collagen VI dystrophy in whom prior genetic analysis is negative. Overall, this study represents a large systematic application of transcriptome sequencing to rare disease diagnosis and highlights its utility for the detection and interpretation of variants missed by current standard diagnostic approaches.
Keywords: Collagen Type VI; High-Throughput Nucleotide Sequencing; Humans; Muscular Diseases; Mutation; Transcriptome

The sensitivity of exome sequencing in identifying pathogenic mutations for LGMD in the United States. - Reddy, Hemakumar M; Cho, Kyung-Ah; Lek, Monkol; Estrella, Elicia; Valkanas, Elise; Jones, Michael D; Mitsuhashi, Satomi; Darras, Basil T; Amato, Anthony A; Lidov, Hart Gw; Brownstein, Catherine A; Margulies, David M; et al. (J Hum Genet, 2017)
The current study characterizes a cohort of limb-girdle muscular dystrophy (LGMD) in the United States using whole-exome sequencing. Fifty-five families affected by LGMD were recruited using an institutionally approved protocol. Exome sequencing was performed on probands and selected parental samples. Pathogenic mutations and cosegregation patterns were confirmed by Sanger sequencing. Twenty-two families (40%) had novel and previously reported pathogenic mutations, primarily in LGMD genes, and also in genes for Duchenne muscular dystrophy, facioscapulohumeral muscular dystrophy, congenital myopathy, myofibrillar myopathy, inclusion body myopathy and Pompe disease. One family was diagnosed via clinical testing. Dominant mutations were identified in COL6A1, COL6A3, FLNC, LMNA, RYR1, SMCHD1 and VCP, recessive mutations in ANO5, CAPN3, GAA, LAMA2, SGCA and SGCG, and X-linked mutations in DMD. A previously reported variant in DMD was confirmed to be benign. Exome sequencing is a powerful diagnostic tool for LGMD. Despite careful phenotypic screening, pathogenic mutations were found in other muscle disease genes, largely accounting for the increased sensitivity of exome sequencing. Our experience suggests that broad sequencing panels are useful for these analyses because of the phenotypic overlap of many neuromuscular conditions. The confirmation of a benign DMD variant illustrates the potential of exome sequencing to help determine pathogenicity.
Keywords: Base Sequence; Distal Myopathies; Exome; Female; Genetic Testing; Glycogen Storage Disease Type II; Humans; Male; Muscular Dystrophies, Limb-Girdle; Muscular Dystrophy, Duchenne; Muscular Dystrophy, Facioscapulohumeral; Mutation; Myopathies, Structural, Congenital; Sequence Analysis, DNA; United States